2020
DOI: 10.3389/fpsyg.2020.01497
|View full text |Cite
|
Sign up to set email alerts
|

Why People Don’t Use Facebook Anymore? An Investigation Into the Relationship Between the Big Five Personality Traits and the Motivation to Leave Facebook

Abstract: This study linked the big five personality traits with motivational factors to leave Facebook based on a survey of 218 former Facebook users. The big five were related with eight main factors retrieved from existing literature. Results showed that neuroticism was positively related to addiction, banality, peer pressure, and privacy while conscientiousness was negatively related to peer pressure, addiction, annoyance, and emergence of new platforms. Openness was positively related with banality but negatively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…In one study however, Yaman (2020) investigates addiction to the social networking service of Facebook and free-time satisfaction in university students; and reports no relationship between Facebook addiction risk and one's satisfaction with how one spends free time. This finding needs to be interpreted however, under the light of the fact that the Facebook social network is not as popular as it used to be among the younger generation (Hong & Oh, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…In one study however, Yaman (2020) investigates addiction to the social networking service of Facebook and free-time satisfaction in university students; and reports no relationship between Facebook addiction risk and one's satisfaction with how one spends free time. This finding needs to be interpreted however, under the light of the fact that the Facebook social network is not as popular as it used to be among the younger generation (Hong & Oh, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Prior empirical investigations have determined various antecedents of leaving social media. 18 Building on the current literature, Hong and Oh 8 listed eight more prevalent reasons for social media withdrawal: the concern for privacy, the appearance of new competitive platforms, peer or family pressure, triviality/banality/irrelevance, annoying or deceptive content, information overload, fear of addiction, and wasting time. Moreover, other authors 15 , 20 , 21 reported SMF as a somehow less apparent, but equally important, reason for the decline in active user numbers.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 4 On the other hand, some statistics reveal that 42% of Facebook users in the United States have taken a break from checking the site for several weeks or more and 26% have removed the app from their mobile phones. 5 Moreover, several different studies showed that some users of well-known social media platforms are considering temporary disconnection from Instagram, 6 , 7 Facebook, 6 , 8 WeChat, 9 MySpace, 10 WhatsApp, 11 or Twitter. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Smith et al ( 1996 ) have defined information privacy as people's capability to manage when, how, and to what extent their personal information is accessed. Concerns over information privacy may include anxiety about information privacy practices by organizations, such as collecting personal information, unauthorized secondary use of personal information, errors in dealing with personal information, and inappropriate access to personal information (Smith et al, 1996 ; Hong and Oh, 2020 ). Privacy concerns increase when users are uninformed about who is collecting their personal information, how SNSs get their information, or for what purposes the information is used (Nowak and Joseph, 1995 ; Lanier and Saini, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, SNS users create accounts to discover other people with similar interests or experiences; this requires them to share certain personal information with both friends and strangers or to establish business contacts. While an increasing number of users have joined various SNSs, their privacy concerns persist (Xu et al, 2011 ; Mahmoodi et al, 2018 ; Hong and Oh, 2020 ). Certainly, with the increased use of the Internet, social networking, and other forms of information sharing (IS), privacy concerns remain a topic of much research and discussion (Bergström, 2015 ; Choi, 2016 ; Kim, 2016 ).…”
Section: Introductionmentioning
confidence: 99%